2022
DOI: 10.1021/acsapm.2c00487
|View full text |Cite
|
Sign up to set email alerts
|

Transparent, Antifreezing, Ionic Conductive Carboxymethyl Chitosan Hydrogels as Multifunctional Sensors

Abstract: By a simple strategy of immersion in a CaCl 2 solution, carboxymethyl chitosan hydrogels exhibited ultralowtemperature freezing resistance below −50 °C. In addition, the introduction of electrolyte ions endowed the hydrogels with electrical conductivity, showing stable and reversible sensitivity to human activity, such as finger bending, pressing, and pharyngeal swallowing. The conductive carboxymethyl chitosan hydrogels could even be assembled into a two-dimensional integrated array of contact sensors, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…The results in the previous sections indicate that the Ca 2+ ion endows the Aniso-Ca 1.5 2+ hydrogel with fixed anisotropic structure, mechanical enhancement, improved ionic conductivity, water retention capability, and antifreezing properties, enabling the composite hydrogel to potentially work as an ion sensor. The working mechanism of Ca 2+ -containing anisotropic hydrogel is illustrated in Figure a. Upon deformation (such as compression), the gap between polymer network chains near the deformed area narrows, blocking the ion transport inside the hydrogel.…”
Section: Resultsmentioning
confidence: 94%
“…The results in the previous sections indicate that the Ca 2+ ion endows the Aniso-Ca 1.5 2+ hydrogel with fixed anisotropic structure, mechanical enhancement, improved ionic conductivity, water retention capability, and antifreezing properties, enabling the composite hydrogel to potentially work as an ion sensor. The working mechanism of Ca 2+ -containing anisotropic hydrogel is illustrated in Figure a. Upon deformation (such as compression), the gap between polymer network chains near the deformed area narrows, blocking the ion transport inside the hydrogel.…”
Section: Resultsmentioning
confidence: 94%
“…tissue engineering, drug delivery, cartilage replacement, wound healing, biosensors, energy harvesting, soft robotics and electronic devices. [4][5][6][7][8][9][10][11][12][13][14][15][16] In general, hydrogels are prepared by cross-linking of the polymer chains either through covalent bonding or promoting van der Waals interactions, or via physical cross-linking. 17 Unfortunately, inferior mechanical properties, structural inhomogeneity in their network and lower water resistance of the hydrogels inhibit their development and application in various areas.…”
Section: Introductionmentioning
confidence: 99%
“…Carboxymethyl chitosan (CMCS), an important derivative of chitosan, exhibits excellent properties including increased water solubility and better biocompatibility. [23] PA@Fe is composed of PA (protocatechualdehyde) and ferric iron (Fe) through the catechol-metal ion coordination bond and establish Schiff base bond with CMCS. In addition, it is reported that PA has several useful characteristics such as proapoptotic, antibacterial properties and good biocompatibility.…”
Section: Introductionmentioning
confidence: 99%